Perbedaan Hasil Masase Perineum dan Kegel Exercise terhadap Pencegahan Robekan Perineum pada Persalinan di Bidan - Sri Rahayu; Sri Sumarni; Umaroh Umaroh (Poltekkes Kemenkes Semarang, 2015)
The aim of this tsudy is to know the difference result of perineal massage and Kegel exercise toward preventing of perineal laceration during labor in the Independent Midwives are close to the District of Semarang. This study is pre experimental research with posttest only design. The population in this stdy is the third trimester pregnant woman who was more than 35 weeks gestational age. The subject of this study were concisted of 18 women as a group one who have done perineal massage beforehand. However, the same number of them have done Kegel exercise from 35 weeks until at term as a group two. The sampling used in this study was a simple random sampling. A group one was tought with perineal massage from 35 weeks until at term. On the other hand, group two was tought with Kegel exercise from 35 weeks until at term. Data about perineal laceration was collected from partogram when they delivered baby. The data was analisd by Man Whitney test. The result of this studi is 77,8 % of group woman who done perineal massage faced first degree of perineal laceration. However, there are only 50 % woman who done Kegel exercise, got first degree of perineal laceration. There is a difference results of perineal massage and Kegel exercise toward preventing of perineal laceration during labor in the Independent Midwives are close to the District of Semarang, which is showed by p value at 0,037. Care provider especially midwive has to service the pregnant woman and encourage to them for doing perineal massage from 35 weeks gestational age until at term.